Welcome to your brain : why you lose your car keys but never forget how to drive and other puzzles of everyday life - Aamodt, Sandra. frey50; Wang, Sam, 1967- (New York : Bloomsbury : Distributed to the trade by Macmillan, 2008)
We use our brains at practically every moment of our lives, and yet few of us have the first idea how they work. Much of what we think we know comes from folklore: that we only use 10 percent of our brain, or that drinking kills brain cells. These and other myths are wrong, as shown by neuroscientists who have spent decades studying this complex organ. However, most of what they have learned is not known to the world outside their laboratories. Here, the authors dispel common myths about the brain and provide a comprehensive, useful overview of how it really works. You'll discover how to cope with jet lag, how your brain affects your religion, and how men's and women's brains differ. With accessible prose decorated by charts, trivia, quizzes, and illustrations, this book is suitable for quick reference or extended reading.--From publisher description.
Includes index.
Keywords: Brain; Neurophysiology